The inverse nodal problem for a differential operator with an eigenvalue in the boundary condition - Koyunbakan, Hikmet (Pergamon-Elsevier Science Ltd, 2008)
We consider the Sturm-Liouville problem with an eigenvalue dependent boundary condition. In this work, by using method of Yang [X.F. Yang, A solution of the inverse nodal problem, Inverse Problems 13 (1997) 203-213.], we reconstruct the potential of the Sturm-Liouville problem with an eigenvalue in the boundary condition from nodal points (zeros of eigenfunctions). Also, we give a uniqueness theorem. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Sturm-Liouville operator; Nodal point; Eigenvalue